4x+5y>-5 , -5x+3y=3

Subtract 5y from both sides of the inequality.

4x>-5-5y or -5x+3y=3

Divide each term by 4 and simplify.

Divide each term in 4x>-5-5y by 4.

4×4>-54+-5y4 or -5x+3y=3

Cancel the common factor of 4.

Cancel the common factor.

4×4>-54+-5y4 or -5x+3y=3

Divide x by 1.

x>-54+-5y4 or -5x+3y=3

x>-54+-5y4 or -5x+3y=3

Simplify each term.

Move the negative in front of the fraction.

x>-54+-5y4 or -5x+3y=3

Move the negative in front of the fraction.

x>-54-5y4 or -5x+3y=3

x>-54-5y4 or -5x+3y=3

x>-54-5y4 or -5x+3y=3

x>-54-5y4 or -5x+3y=3

Subtract 3y from both sides of the equation.

x>-54-5y4 or -5x=3-3y

Divide each term by -5 and simplify.

Divide each term in -5x=3-3y by -5.

x>-54-5y4 or -5x-5=3-5+-3y-5

Cancel the common factor of -5.

Cancel the common factor.

x>-54-5y4 or -5x-5=3-5+-3y-5

Divide x by 1.

x>-54-5y4 or x=3-5+-3y-5

x>-54-5y4 or x=3-5+-3y-5

Simplify each term.

Move the negative in front of the fraction.

x>-54-5y4 or x=-35+-3y-5

Dividing two negative values results in a positive value.

x>-54-5y4 or x=-35+3y5

x>-54-5y4 or x=-35+3y5

x>-54-5y4 or x=-35+3y5

x>-54-5y4 or x=-35+3y5

-(5)/(4)-(5y)/(4)","isGrey":false,"dashed":false,"holes":[]},{"ascii":"x=-(3)/(5)+(3y)/(5)","isGrey":false,"dashed":false,"holes":[]}],"asymptotes":[],"segments":[],"areaBetweenCurves":[],"points":[],"HasGraphInput":true}” class=”GraphWrapper”>

Find the Union (or) 4x+5y>-5 , -5x+3y=3